Harvest weed seed control of Italian ryegrass [Lolium perenne L. ssp. multiflorum (Lam.) Husnot], common ragweed (Ambrosia artemisiifolia L.), and Palmer amaranth (Amaranthus palmeri S. Watson). (August 2019) - Beam, Shawn C.; Mirsky, Steven; Cahoon, Charlie; Haak, David; Flessner, Michael
Abstract: Herbicide resistance is a major problem in United States and global agriculture, driving farmers to consider other methods of weed control. One of these methods is harvest weed seed control (HWSC), which has been demonstrated to be effective in Australia. HWSC studies were conducted across Virginia in 2017 and 2018, targeting Italian ryegrass in continuous winter wheat as well as common ragweed and Palmer amaranth in continuous soybean. These studies assessed the impact of HWSC (via weed seed removal) on weed populations in the next year's crop compared with conventional harvest (weed seeds returned). HWSC reduced Italian ryegrass tillers compared with the conventional harvest at two locations in April (29% and 69%), but no difference was observed at a third location. At wheat harvest, HWSC at one location reduced Italian ryegrass seed heads (41 seed heads m −2 ) compared with conventional harvest (125 seed heads m −2 ). In soybean, before preplant herbicide applications and POST herbicide applications, HWSC reduced common ragweed densities by 22% and 26%, respectively, compared with the conventional harvest plots. By soybean harvest, no differences in common ragweed density, seed retention, or crop yield were observed, because of effectiveness of POST herbicides. No treatment differences were observed at any evaluation timing for Palmer amaranth, which is attributed to farmer weed management (i.e., effective herbicides) and low weed densities making any potential treatment differences difficult to detect. Across wheat and soybean, there were no differences observed in crop yield between treatments. Overall, HWSC was demonstrated to be a viable method to reduce Italian ryegrass and common ragweed populations.